2006
DOI: 10.12702/1984-7033.v06n01a03
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Capsicum accessions using RAPD markers

Abstract: Genetic diversity among Capsicum accessions using RAPD markers ABSTRACT -The genus Capsicum has 27 species, being five domesticated and 22 semi-domesticated and wild ones. For an enhanced use of the germplasm in breeding programs it is necessary to know the accessions in the collections, to identify them and evaluate the genetic diversity. Objectives of this research were to quantify the genetic diversity among 70 Capsicum accessions, confirm their identification and verified possible duplicated accessions, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 18 publications
0
25
0
4
Order By: Relevance
“…The traditional method of distinctness, uniformity and stability (DUS) testing is time-consuming and expensive, requiring large areas of land and skilled personnel, and is often subjective due to environmental influences (Singh et al, 2004). Further, taxonomy of the genus Capsicum is confusing and sometimes it is difficult to identify an accession using only subjective morpho-agronomic data (Costa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional method of distinctness, uniformity and stability (DUS) testing is time-consuming and expensive, requiring large areas of land and skilled personnel, and is often subjective due to environmental influences (Singh et al, 2004). Further, taxonomy of the genus Capsicum is confusing and sometimes it is difficult to identify an accession using only subjective morpho-agronomic data (Costa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These markers have proven to be very useful in assessing genetic diversity and phylogeny, characterization of germplasm and detection of duplicates, parental verification in crosses, gene tagging in marker assisted breeding and gene cloning in genetic transformation (Costa et al, 2006). The application of RFLPs for genetic diversity is limited because it requires the use of radioactivity and is labour intensive (Nahm et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As técnicas de análises multivariadas têm sido empregadas para a quantificação da divergência genotípica e fenotípica em várias espécies de hortaliças (COSTA et al, 2006;SUDRÉ et al, 2005). O estudo de divergência permite conhecer o grau de seleção da variabilidade genética das populações vegetais e subsidia a seleção de genitores geneticamente mais divergentes, que poderão ser utilizados em intercruzamentos com possibilidade de aumentar a probabilidade de recuperação de segregantes superiores em gerações avançadas (CRUZ & CARNEIRO, 2003).…”
Section: Introductionunclassified
“…Among all molecular plant markers, RAPD is best, suitable tool for poorly studied species such as ginger, because it requires no prior information on the genome and is also cost-effective. Several studies have reported the successful use of RAPD markers to assess genetic diversity and phylogenetic relationship in different crop species [116][117]. Being a poorly studied genome, little information is available on the molecular characterization of gingers investigated the diversity within and among Zingiber species and found that Z. officinale from different geographical origin were identical in phylogenetic analysis and metabolic profiling.…”
Section: Molecular Marker Analysis Of Z Officinalementioning
confidence: 99%